Successfully Treated Acute Interstitial Pneumonia - Marija Gomerčić Palčić; Ivan Turalija; Luka Vrbanić; Ivana Folnožić; Eugenija Basioli Kasap; Monika Ulamec (Acta Clinica Croatica, 2022)
Acute interstitial pneumonia (AIP) is a rare idiopathic interstitial pneumonia with histology finding of diffuse alveolar damage (DAD). It is characterized by progressive hypoxic respiratory failure, high mortality rate, and absence of guidelines for its treatment. Here we present a case of a 64-year-old woman with progressive dyspnea, acute respiratory failure, diffuse bilateral reticulonodular opacities on standard chest radiograph, diffuse ground-glass opacities on computed tomography, and biopsy proven DAD. Diagnosis of AIP was established after extensive work-up that excluded the known risk factors for acute respiratory distress syndrome. Oxygen therapy and high-dose parenteral corticosteroids led to gradual improvement and resulted in complete respiratory recovery. Since there are no existing guidelines for treating AIP, more case reports and case series if not randomized control trials are warranted in order to define the most effective therapeutic modality.